Durable, self-healing, superhydrophobic fabrics from fluorine-free, waterborne, polydopamine/alkyl silane coatings. Issue 54 (5th July 2017) - Wang, Hongxia; Zhou, Hua; Liu, Shuai; Shao, Hao; Fu, Sida; Rutledge, Gregory C.; Lin, Tong
Abstract : Superhydrophobic fabrics prepared from a polydopamine coating show high water repellency, good durability and self-healing property. Abstract : Superhydrophobic fabrics have diverse applications in both textile and non-textile fields. Most of the waterborne materials for superhydrophobic treatment of fabrics use fluoro-containing substances, which have potential issues with bio-accumulation in both the human body and animals. Fluorine-free waterborne coatings are highly desirable for superhydrophobic treatment. In this study, we have prepared a fully waterborne coating solution through dispersion of an alkyl silane (hexadecyl trimethoxysilane) in an aqueous dopamine solution. After applying to fabrics through a wet-chemical process, the coating made the fabrics have a superhydrophobic surface with a water contact angle and a sliding angle of 163° and 8.6°, respectively. The treated fabrics are durable enough to withstand multiple washing. The coating is self-healable against acid/base etching and plasma damage. Such a fluorine-free, durable coating may be useful for the development of various superhydrophobic fabric products.